Study on prevalence of hypertension, diabetes mellitus and their few risk factors among rural women in Ghaziabad - Singh, Narendra (International Journal Of Community Medicine And Public Health, 2017)
Background: With rapid urbanisation in National Capital Region, Ghaziabad, associated life style diseases like hypertension, diabetes mellitus are also increasing. For an effective preventive program, it is mandatory to know prevalence and relevant risk factors. Many studies among men have been conducted, this study was undertaken to find out prevalence, and associated factors solely among rural women in Ghaziabad. Methods: A pretested Performa was administered to all non-pregnant women coming to a health centre. Information on medical and family history, dietary habits, physical activity, blood pressure, blood sugar, height, weight etc. was recorded. For statistical analyses, SPSS-16 software was used. Results: Out of total 569 participants, 59 were having hypertension, showing a prevalence of 10.36 %, 44 were having family history of hypertension with a prevalence of 7.73%. 93 were found to be Diabetics, with a prevalence of 16.34% and family history of diabetes among 57, i.e. 10.36% in study group. Overall 134, (23.55%) had abnormally higher BMI, age group with highest prevalence of BMI was also having highest diabetes and hypertension cases. This age group was found to be doing just mild physical activity. Conclusions: This study gives insight in heavy burden of hypertension, diabetes, and associated risk factors in rural women folks in a rural health centre of Ghaziabad. Life style modifications, more physical activities, dietary modifications with lesser salt ,fats will go in long way of reducing burden of these diseases and risk factors.